Size-resolved airborne in-situ measurements of aerosol particle number concentrations during the BACSAM II campaign in April 2024 - David J Simon; Jonas Schaefer; Markus Hartmann; Bruno Wetzel; Frank Stratmann (PANGAEA, 2025)
During research flight 09 (RF09) of the airborne measurement campaign Boundary layer and Aerosol and Cloud Study in the Arctic, based on aircraft and T-Bird Measurements (BACSAM) II, size-resolved particle number concentrations were measured at a temporal resolution of 1 Hz. RF09 took place on 25 April 2024 and started and ended in Longyearbyen, Svalbard. The flight was carried out with the research aircraft Polar 6 (P6) of the Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research (AWI). The P6 dragged the towed-body system T-Bird, which was developed by AWI, with its aerosol payload as a significant contribution by the Leibniz Institute for Tropospheric Research (TROPOS). The T-Bird is described in detail in Juranyi et al., 2025, details concerning RF09 can be found in Simon et al., 2025 (in prep). Onboard the T-Bird, particle number concentrations were measured with the optical particle counter Portable Optical Particle Spectrometer (POPS, Handix Scientific Inc., USA, Gao et al., 2016, https://doi.org/10.1080/02786826.2015.1131809) in 12 size bins in the particle size range of approximately 185 nm to 3300 nm. The left and right bin boundaries are given in nm in the header of the data file for each column, which contains the particle number concentrations in the respective size range in units of #/ccm. Near-isokinetic sampling was established throughout the flight and the transmission efficiency of the tubing leading from the T-Bird extquotesingles aerosol inlet to the POPS was close to unity (Simon et al., 2025 (in prep.)). Data are only reported for the times the T-Bird was winched out and flying below the aircraft. All data have been corrected to standard conditions (1013.0 hPa and 273.15 K).